GENETIC VARIANCE, HERITABILITY AND CORRELATION IN SOME TRAITS OF BREAD WHEAT (TRITICUM AESTIVUM L.) UNDER DIFFERENT NITROGEN LEVELS - BAYAR , DALAL; ASKANDER, HAJAR. S. A. (Journal of Duhok University, 2023)
Twelve genotypes of bread wheat, with four levels of nitrogen (0, 75, 150, 225 kg N ha-1). were grown in split block design with three replication in growing season (2021), correlation, phenotypic and genotypic coefficient of variation, heritability and genetic advance were estimated for (days of 75% flowering, plant height, grain filling, grain yield, number of spike/plant, spike length, grain weight, flag leaf area, biomes, protein and harvest index. Highly significant and positive correlation found between grain yield and grain weight, harvest index and protein. While significantly 5% with plant height. Broad sense heritability was found to be low for the all studied traits followed by moderate to low values of genetic advance as percent for studied traits